PROFESSIONAL LEXICAL COMPETENCE DEVELOPMENT IN BLENDED LEARNING - Diachok, Nadiia (The Modern Higher Education Review, 2023)
The integration of Ukraine into the world community requires perfect mastery of foreign languages from future professionals. The number of hours allocated to studying a foreign language in institutions of higher education is insufficient for the formation of all types of foreign language competences, in particular, foreign language lexical competence. Possession of lexical competence is part of the system of development of speaking in a foreign language. That is why there is a need to improve the methods, means and technologies of foreign language learning. The purpose of the article is to reveal the role of the process of formation of students’ foreign language lexical competence. To achieve the goal, a questionnaire was conducted among students of a language institution of higher education. The paper presents the data and analysis of the conducted survey. It was concluded that the combination of traditional teaching methods and innovative ones in the process of learning a foreign language makes it possible to intensify the independent activity of students, increases cognitive activity, and contributes to more effective vocabulary development in blended learning. Recommendations are given on facilitating students’ mastery of lexical units in blended learning.